FACTORS AFFECTING THE COMPLIANCE LEVEL OF PROFESSIONAL GIVING CARE (PPA) NUTRITION IN PROVIDING EDUCATION TO PATIENTS AND FAMILIES AT RSUD PROF. DR. H. ALOEI SABOE GORONTALO CITY - FriSandri Riski Daud; Srikit S. Nurkamiden; Lidya Paramitha Moha (Jurnal Ilmiah dr. Aloei Saboe, 2023)
Providing education to patients is greatly influenced by the quality of services provided by PPAs, but not all PPAs are compliant in providing health care, and have a good attitude towards patients. This educatin is carried out to support the return of health fuctions before and optimal health maintenance. This research was conducted at the Nutrition installation of RSUD Prof. Dr. H. Aloei Saboe Gorontalo City by using a Quantitative approach and the type is descriptive research. The data collection method is carried out by distributing questionnaires containing criteria to be analysed including predisposing factors, probable factors, and families. The research subjects were all staff of the Nutrition Installation of RSUD Prof. Dr. H. Aloei Saboe Gorontalo City. The results of the study csn be concluded that Professional Giving Care (PPA) Nutrition has compliance in providing education to patients and families at RSUD Prof Dr. H. Aloei Saboe Gorontalo City, this is shown by (score > 50%) measurement results of each compliance criterion. There are 3 factors that affect the compliance of Professional Giving Care (PPA) nutrition in providing education to patients and families including predisposing factors (knowledge, and attitudes), enabling factors (facilities/infrastructure, work environment, and socialization), and reinforcing factors (management roles and policies). From three factors, knowledge, and attitude are the elements that most influence the level of compliance.